FAKTOR-FAKTOR YANG MEMENGARUHI PERMINTAAN JAGUNG PIPIL (HIBRIDA) DI BATURAJA TIMUR KABUPATEN OKU - Anggraini, Rita; Lastinawati, Endang; Pusvita, Ema (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study has directions to find out the factors that influence the demand for shelled corn (hybrid) in OKU Regency. This research method was carried out using a quantitative method in which the research used multiple linear regression analysis. Data was obtained by distributing questionnaires and data obtained from shelled corn traders in the upper market and in the new market. The results of this study are the factors that influence the demand for loose corn (hybrid) in East Baturaja, namely there are 3 factors including: the price of shelled corn, quality and price of pur chicken. Of the three factors that greatly influence the price of corn at a real level of 1 rupiah, it will reduce the demand for shelled corn by -94.701 kg. The average income of traders at retail stores in East Baturaja is IDR 398,986 per year.